Survey of Scutellonema bradys incidence on marketed yam (Dioscorea spp.) in Benin - Baimey, H.; Coyne, Danny L.; Labuschagne, N. (2009)
A survey was conducted in the different areas in Bénin where yam (Dioscorea spp) are grown. Yam tubers were assessed visually for dry rot disease associated with the yam nematode, Scutellonema bradys. Assessments were made during February and March in 2002 and 2003 on yam for sale on market stalls. Population density of S. bradys was also determined from 65 sampled yam tubers, selected for exhibiting symptoms of dry rot. Differences among yam cultivars, yam species, sites of tuber origin, and agroecological zones (AEZ) of tuber cultivation, were analyzed. A total of 3222 tubers from 110 market stalls were visually assessed for nematode damage. The percentage of tubers with dry rot caused by S. bradys was low (mean of 3.57%). Symptoms of nematode damage were observed most frequently on cultivar Idjekoka and cultivar Krokotonnè (both D. rotundata) and cultivar Kokoro (D. cayenensis). Population density of S. bradys varied considerably among yam cultivars, yam species, sites of origin of tubers, and the AEZ where tubers were grown. Dioscorea rotundata supported the highest (p≤0.05) nematode population density (mean of 488 S. bradys/g tuber peel) and D. alata the lowest (mean of 4 S. bradys/g tuber peel). No S. bradys were recovered from some cultivars, even though tubers appeared to have dry rot symptoms. Nematode population density as high as 1700/g tuber peel was recorded on cv Yoruba dundu (D. rotundata). The highest number of S. bradys were recovered from the sites Bio Amadou Kpara (mean of 3789 S. bradys/g tuber peel), Monne (2609 S. bradys/g tuber peel), and Nangatori (2316 S. bradys/g tuber peel)